Infestation and host specificity of mistletoe parasitic plants in Purwodadi Botanic Garden - Solikin Solikin (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2022)
Mistletoes are aerial hemiparasitic plant that infesting and parasitizing on wild and cultivated plants. They are can be categorized as generalist and specialist mistletoes according to their host plants diversity. Shannon index of the host plants diversity can be used to determine host specificity of mistletoes. Study aimed to know and determine host plants and host specificity of mistletoes in Purwodadi Botanic Garden was conducted in 2013, 2017 and 2021. Data of mistletoes and their hosts species was collected by explorative and descriptive methods in 2013, 2017, and 2021. Recorded data by observation in the fields were species and species number of mistletoes and their hosts. Observation of the misteltoes used binoculars to ditermine the species of the mistletoes. Identification of the mistletoes species and their hosts was conducted directly in the garden and undirectly by making herbarium specimens and taking photographs. The results showed that there were five species of mistletoes infested 142 species, 82 genera and 36 families of host plants namely Dendrophthoe pentandra, Macrosolen tetragonus, Scurrula atropurpurea, Viscum articulatum, and Viscum ovalifolium. There were significantly different between the mistletoe species and their Shannon index of host plants . D. pentandra was the most generalist or the least specialist to host plants with the highest Shannon index value of 2.20±0.10, whereas S. atropurpurea was the least generalist or the most specialist with Shannon index value of 0.16±0.09.